31odernisasi Hukum di Indonesia Adakah -Peran Golongan Borjuis Seperti Di Eropa Barat ?- - Muhammad Syamsudin (Fakultas Hukum Universitas Islam Indonesia, 2006)
The Modernization of law in West Europe, in the process of the modernization was supported by the bourgeois liberal capitalism group. The group was able to changefundamentally the social, cultural political and economic aspects of the EuropeanCommunity who has already established the modem concept of law. Is the condition alsooccured in Indonesia?